2016
DOI: 10.1055/s-0042-101247
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Passive Intestinal Absorption of Medicinal Plant Extract Constituents with the Parallel Artificial Membrane Permeability Assay (PAMPA)

Abstract: At the early drug discovery stage, the high-throughput parallel artificial membrane permeability assay is one of the most frequently used in vitro models to predict transcellular passive absorption. While thousands of new chemical entities have been screened with the parallel artificial membrane permeability assay, in general, permeation properties of natural products have been scarcely evaluated. In this study, the parallel artificial membrane permeability assay through a hexadecane membrane was used to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…However, its applicability is extremely restricted due to its complexity, high cost, and ethical considerations. Several in vitro and in situ methods were developed for the measurement of permeability, including the parallel artificial membrane permeability assay, [24][25][26][27] everted gut sacs, [28][29][30] Ussing side-by-side diffusion chambers, 12,[31][32][33][34] Caco-2 monolayers, [35][36][37] and intestinal perfusion models for example, the rat single-pass intestinal perfusion (SPIP), [38][39][40][41] and the Doluisio technique. 37,[42][43][44] These methods are now well established and frequently used; yet, to assess segmental-dependent intestinal absorption throughout the GIT, rat intestinal perfusion still remain the most significant experimental method.…”
Section: Introductionmentioning
confidence: 99%
“…However, its applicability is extremely restricted due to its complexity, high cost, and ethical considerations. Several in vitro and in situ methods were developed for the measurement of permeability, including the parallel artificial membrane permeability assay, [24][25][26][27] everted gut sacs, [28][29][30] Ussing side-by-side diffusion chambers, 12,[31][32][33][34] Caco-2 monolayers, [35][36][37] and intestinal perfusion models for example, the rat single-pass intestinal perfusion (SPIP), [38][39][40][41] and the Doluisio technique. 37,[42][43][44] These methods are now well established and frequently used; yet, to assess segmental-dependent intestinal absorption throughout the GIT, rat intestinal perfusion still remain the most significant experimental method.…”
Section: Introductionmentioning
confidence: 99%
“…We followed this approach by developing SLNs loaded with vegetable oils from Brazilian flora, which is rich in antioxidant substances. We used a powerful multiphoton imaging technique (MPT-FLIM) to verify interaction between formulations and skin in human volunteers, as well as ex vivo (Franz cell) tests of skin permeation [18,19,24,25,26]. …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that deglycosylation of such compounds by β‐glucosidase in the small intestine and by the colonic microflora is often required before absorption can occur. The flavonoids aglycones, either occurring as such in plants or resulting from hydrolysis, displayed various permeability behaviors (Petit et al, ).…”
Section: Discussionmentioning
confidence: 99%